Research That Hurts Or Research That Helps? A Critical Framework for Adult Education Inquiry and People With Intellectual Disabilities - Rachel Gorman (Adult Education Research Conference, 2000)
This study provides two important caveats to educators involved in work with adults with intellectual disabilities: we must pay close attention to the structures we operate within, and we must carefully interrogate our purpose and our methods.